Knowledge, Attitudes, and Practices Toward Coronavirus Disease 2019 in the Central Area of Iran: A Population-Based Study - Moradzadeh, Rahmatollah; Nazari, Javad; Shamsi, Mohsen; Amini, Saeed (Frontiers in Public Health, 2020)
Background: The spread of Coronavirus Disease of 2019 (COVID-19) pandemic has imposed high threats on global health, life and work style and social and economic development. The current study was aimed to extract knowledge, attitude and practices related to COVID-19 among general population in central area of Iran. Method: A cross-sectional study was conducted in Arak city between April and May, 2020. Stratified random sampling was applied to select the study participants. Phone interview was applied to collect the data. Data was collected using the questionnaire constructed and validated in this study. The questionnaire included demographic variables and items about knowledge, attitude and practice towards COVID-19. The descriptive and inferential analysis was conducted in STATA software. Results: Totally, 544 participants were completed the questionnaire. 76% of the participants accounted COVID-19 as a high threat one month from the onset of COVID-19. From the maximum attainable scores of 1, 6 and 6, for COVID-19 related knowledge, attitude and practice, means 0.77(0.13), 4.97(0.63) and 5.35 (0.70) was obtained, respectively. Females had higher practice score (5.4±0.6). The participants with family history of heart and respiratory diseases had significantly higher attitude and practice scores. SMS from the ministry of health had significant impact on the knowledge, attitude and practice scores (p<0.05). Conclusion: Higher attention should be paid to increase men and housewife group knowledge, attitude and practice. COVID-19 preventive messaging from the ministry of health were among the most influential methods of increasing knowledge that attracted public attention.